Evaluasi Usability Pada Game Dota 2 Menggunakan Metode Heuristic Evaluation - Fathoni Alim Rosyidi; Satrio Hadi Wijoyo; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dota 2 is a Free-To-Play (F2P) game with the Online Multiplayer Battle Arena (MOBA) type, this game is a version of world of warcraft 3 which was developed by Valve Corporation in 2011. On the Dota 2 steam game platform it has a rating view that very good, which is mostly positive, and had become the most popular game in 2016 by being played by 1.2 users online simultaneously (statista, 2018). But based on the game Dota 2 www.statista.com has experienced a decline in players and now there are 700 thousand active players who play the DotA 2 game (statista, 2018). So that by knowing the problems in specific games, game companies can find out what needs to be improved in the game. The heuristic evaluation used is the usability heuristic method which covers 9 aspects. 9 aspects are: (1) visibility of system status, (2) offer real world object, (3) user control and freedom, (4) consistency and standarts, (5) error prevention, recognition rather than recall, (6) flexibility and efficiency of use, (7) aesthetic and minimalist design, (8) help user recognize, (9) diagnose and recover from error. The evaluation using the heuristic method resulted in 22 problems found, consisting of 2 cosmetic problems, 5 minor problems, 13 medium problems, and 2 major problems. the heuristic principle that is most commonly found is the principle of MA08 (Aesthetics and Minimalist Design) with the finding percentage of 22.72% with a severity rating of 3, which means the problem is at the medium level.